Agricultural Inputs Marketing In Haryana: Role of Government in Agricultural Inputs Marketing in Haryana (Journal of Advances and Scholarly Researches in Allied Education, 2012)
In Haryana, the Government plays an important role on thedistribution and marketing of tractors, fertilizers, pesticides and seeds. Theprices of these products are determined by the manufacturers in consultationwith the Government particularly in case of fertilizers, seeds andpesticides.  These are covered under theEssential Commodities Act. The marketing of tractors is made through their dealersor their agencies allocated at district headquarters or at bigger cities